Light avaliability at the dry and rainy seasons in agrossivicultural system under different fertilizations - S. A. H Abreu; M. P. Santos; F. N. Calil; N. P. R. Reges; R. B. Costa; P. A. Ximenes; P. P. Cunha (Scientific Electronic Archives, 2017)
This study was conducted in a agrossilvicultural system with two years of deployment, located in Goiânia, Goiás, using tree component as the species Tectona grandis L. f. This objective was evaluate the radiation incidence in the seasons dry and rainy under different fertilization. The design was a randomized block, in split plot, factorial arrangement 4 x 2 x 2. The plots received the factors fertilization and measurement of height, being four types of fertilization (control, NPK, sewage sludge and cattle manure) and two heights measure (soil level and 1.3 m above the soil). The subplots were allocated two seasons (dry and rainy), with four repetitions (blocks). They evaluated the photon flux density (PFD) in μmol.m-2.s-1 and the percentage of shading in the understory. The types of fertilizer did not influence the soil fertility and the light avaliability in any of the seasons and heights of measurement. The percentage (%) shading differed only at soil level, being higher in the rainy season compared to season dry (37.18 vs. 19.80%). In the dry season is reduced (%) shading and the consequent increase in photon reflectance rate at soil level in the agrossilvicultural system in initial stage.